Mouse immunoglobulin antibodies require complement for neutralization of mouse retroviruses. - Sarma, P S (1983)
The addition of guinea pig complement was found to enhance the neutralizing capacity of mouse antibodies directed against the endogenous ecotropic murine leukemia viruses. The same immune sera, when tested without complement, had low or negligible neutralizing capacities, regardless of whether freshly harvested, unfrozen virus was used to preserve virus infectivity. Antibodies in high titers were found in sera from NFS congenic mice carrying the mouse leukemia virus inducing locus Akv-2. These mouse antibodies were type specific and failed to neutralize either Friend or Moloney leukemia virus. The mouse serum immunoglobulin fraction containing the complement-dependent antibodies was tentatively identified as immunoglobulin M.